REFORMA AGRARIA DI BIDANG TANAH PERCATON - Umi Supraptiningsih (Faculty of Law, Universitas Brawijaya, 2021)
The loss of Village treasure land (tanah kas desa) known as Percaton becomes a severe concern. Percaton land is lost or has been converted its ownership because an application has been submitted. Regarding this, the land is considered either as state land or transferred to another party. Percaton land is part of the village treasury land, which is used for the welfare of the village, including the village head and the officials. In line with this, this paper aims to explore the Agrarian Reform in terms of village treasure land protection. It was based on the finding of the study that implementing qualitative research design. The data was obtained by conducting interviews, observation, and documentation (which is taken from news and jurisprudence). The finding revealed that the loss and the release of Percaton (the transfer of ownership) were happened because of the system that can provide legalcertainty. The parties who are supposed to protect and be responsible for the existence of village treasury lands, in fact, make the village treasury lands unable to function which is in accordance with the purpose of the village treasury lands. The followings are some reasons why the ownership of Percatonis lost and transferred to other parties. First, the management ofpercatonland –the land managed by the head of the village and the officials during their tenure-is complicated because they have notyet wholeheartedly and voluntarily surrendered the percaton land to their successor (the next leaders). Second, an independent and effective government monitoring and evaluation of the management of Percaton lands has not been implemented yet. The monitoring and assessment should be based on article 112 jo article 115 point g of the Village Law No. 11 of 2014 are carried out by the city/ regency government vertically and Village Consultative Agency horizontally.